The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15570/actaapa.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dermatological complaints among healthcare professionals during the COVID-19 outbreak in Turkey

Abstract: From April 5th to 12th, 2020, between the 25th and 32nd days after the first COVID-19 case in Turkey, a self-administered online questionnaire (SurveyMonkey®) consisting of 90 questions was conducted for doctors and nurses that voluntarily participated in the study. We aimed to reduce the risk of bias in the questions posed to the participants by carrying out this retrospective study in the early phase of the COVID-19 outbreak. The first part of the questionnaire examined subjects such as demographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 24 publications
(33 reference statements)
3
93
0
Order By: Relevance
“…After the screening of the titles and abstracts, we removed 2671 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39] in this metaanalysis that met our inclusion criteria.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After the screening of the titles and abstracts, we removed 2671 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39] in this metaanalysis that met our inclusion criteria.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Main characteristics of the studies included in our systematic review and metaanalysis are shown in Table 1 [26,28,[30][31][32][33]35,36,38,39], two studies were conducted in Europe [34,37], one study was conducted in South America [27], and one study included HCWs from 10 countries [29]. All studies were cross-sectional, while 13 studies [26][27][28][29][30][32][33][34][35][36][37][38][39] used a convenience sample method and one study [31] used a purposeful sampling method. Assessment of adverse events was self-reported through questionnaires in 13 studies [26][27][28][29][30][31][32][33][34][35][37][38][39], while in one study [36] a clinical diagnosis was performed.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations